Pengembangan Multimedia Interaktif Untuk Meningkatkan Keterampilan Proses Sains Siswa Pada Materi Struktur dan Fungsi Jaringan Tumbuhan Kelas XI IPA SMA Xaverius I Jambi - Hastuti Wibowo; Syamsurizal Syamsurizal; Upik Yelianti (Universitas Jambi, 2013)
Research and development of interactive multimedia development model is adapted from Lee & Owens;the steps were analysis, design, development, implementation, and evaluation. The results of learningmaterials proportion analysis based curriculum: tissues: organs: totipotensi was 40%: 40%: 20%. Theresults of need analysis of science process skills indicated that students are lack of ability in terms ofgrouping and concluding skill. The analysis also reveals that students need multimedia, which isinteresting and aesthetics. In the design phase, developers create a storyboard based on the results of theanalysis. In development stage, we input all information in storyboard to the media. According to mediaexperts, the product is scored well and very well. Trials phase is conducted in a small groups and largegroups. The results of tests shows that the skills of students increased from 69.34 to 89.30, and knowledgeof students also increased from 75.7 to 91.9. The effectiveness of interactive multimedia structure andfunction of plant tissue seen by the changes in knowledge, performance, and the positive response ofstudents using interactive multimedia and facilitate students doing science process skills.